Microbial arsenite oxidation with oxygen, nitrate, or an electrode as the sole electron acceptor. (1st June 2017) - Nguyen, Van Khanh; Tran, Huong T; Park, Younghyun; Yu, Jaecheul; Lee, Taeho
Abstract: The purpose of this study was to identify bacteria that can perform As(III) oxidation for environmental bioremediation. Two bacterial strains, named JHS3 and JHW3, which can autotrophically oxidize As(III)–As(V) with oxygen as an electron acceptor, were isolated from soil and water samples collected in the vicinity of an arsenic-contaminated site. According to 16S ribosomal RNA sequence analysis, both strains belong to the ɤ -Proteobacteria class and share 99% sequence identity with previously described strains. JHS3 appears to be a new strain of the Acinetobacter genus, whereas JHW3 is likely to be a novel strain of the Klebsiella genus. Both strains possess the aioA gene encoding an arsenite oxidase and are capable of chemolithoautotrophic growth in the presence of As(III) up to 10 mM as a primary electron donor. Cell growth and As(III) oxidation rate of both strains were significantly enhanced during cultivation under heterotrophic conditions. Under anaerobic conditions, only strain JHW3 oxidized As(III) using nitrate or a solid-state electrode of a bioelectrochemical system as a terminal electron acceptor. Kinetic studies of As(III) oxidation under aerobic condition demonstrated a higher V max and K m from strain JHW3 than strain JHS3. This study indicated the potential application of strain JHW3 for remediation of subsurface environments contaminated with arsenic.